Environmental effects of ozone depletion and its interactions with climate change: Progress report, 2015 - Andrady, A.; Aucamp, P.; Austin, A.; Bais, A.; Ballaré, C.; Barnes, P.; Bernhard, G.; Björn, L.; Bornman, Janet; Erickson, D.; De Gruijl, F.; Häder, D.; et al. (Royal Society of Chemistry, 2016)
The Environmental Effects Assessment Panel (EEAP) is one of three Panels that regularly informs the Parties (countries) to the Montreal Protocol on the effects of ozone depletion and the consequences of climate change interactions with respect to human health, animals, plants, biogeochemistry, air quality, and materials. The Panels provide a detailed assessment report every four years. The most recent 2014 Quadrennial Assessment by the EEAP was published as a special issue of seven papers in 2015 (Photochem. Photobiol. Sci., 2015, 14, 1-184). The next Quadrennial Assessment will be published in 2018/2019. In the interim, the EEAP generally produces an annual update or progress report of the relevant scientific findings. The present progress report for 2015 assesses some of the highlights and new insights with regard to the interactive nature of the effects of UV radiation, atmospheric processes, and climate change.